(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2026)
Turbinaria ornata is a type of brown alga that has high potential in the field of pharmanutraceuticals, primarily due to its content of bioactive compounds. T. ornata can serve as a source of extracts for the manufacture of medicinal preparations. However, the lack of knowledge among coastal communities about the potential of this alga has resulted in many ignoring its sustainability. A solution that can be offered is to provide outreach on how to preserve this alga. Cultivation is the right solution to address the scarcity of algae in marine waters. In developing the brown macroalgae T. ornata, training in algae cultivation is necessary. The techniques that can be applied include the bottom culture method, floating raft culture method, and longline method. These techniques are commonly used, with attention to the selection of cultivation sites, sea water currents, sea water quality, and optimal circulation being key to successful algae farming. The purpose of community service implementation is to provide information through training on technology for cultivating this alga. The targeted outcome is for the community to understand the techniques of cultivating algae. The mandatory outputs include publication in a national journal, online media, and partners for ongoing collaboration.